The ford resource and engagement centre (frec) programme's contribution to mitigating poverty : perspectives from early exit and currently enrolled participants - Lombard, A. (Antoinette) (University of Pretoria, 2025)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2024.